UPAYA PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MELALUI PENDEKATAN POLYA - Iding Rosadi; Rifqi Hidayat; Jajang Rahmatudin (Integral : Pendidikan Matematika, 2018)
This thesis entitled an effort to improve students' understanding of mathematical concepts insolving problem solving through Polya. The purpose of this research is to know theimprovement of students' concept comprehension in solving the story problem through Polyaapproach. This research uses Classroom Action Research (PTK) which is implemented inClass VII A MTs PUI Cilimus Lesson Year 2017/2018. Adapaun source data used is theobservation of students to know the development of student activities during learning andtests to determine the improvement of students' concepts in understanding the problem. Theresulting data will be analyzed by descriptive method. The theoretical basis used is thetheory of concept comprehension, problem solving and Polya approach. Based on dataanalysis done, it can be concluded that by using Polya approach in solving problem solvingproblem there is increasing understanding of student concept. This is evident from the resultsof the test in the second cycle of 48% of the initial test is only 30% and in the final testreached 78%. While the concept of students understanding also increased by 22.5% fromcycle 1 of 75% and cycle 2 of 97.5%. Therefore, the method of Polya approach is suggestedto be used to improve the concept of students in solving the problem solving problem.Keywords: Conceptual understanding, problem solving, Polya approach